Mbd2 deficiency alleviates retinal cell apoptosisvia the miR-345-5p/Atf1 axis in high glucoseinjury and streptozotocin-induced diabetic mice - Yanni Ge (Elsevier, 2021)
DNA methylation is considered to play an important role in the development of diabetic retinopathy. Here, our goal was to investigate the precise role of methyl-CpG binding domain protein 2 (Mbd2) in the apoptosis of retinal ganglion cells (RGCs) in the early diabetic retina. Mbd2 was significantly upregulated after high glucose (HG) treatment and played a proapoptotic role in RGCs during HG-induced apoptosis. Combining ChIP and gene microarray datasets, the results showed that Mbd2 possessed potential binding sites for miR-345-5p, thereby elevating the expression levels of miR-345-5p via the enhancement of promoter demethylation. Activating transcription factor 1 (Atf1) played an anti-apoptotic role during the process of apoptosis in RGCs and acted as the target gene for miR-345-5p. Furthermore, the number of surviving RGCs in the diabetic retina was increased in Mbd2-knockout mice when compared with wild-type mice and the visual function became better accordingly. Collectively, our data demonstrated that the HG-induced overexpression of Mbd2 in the retina was partly responsible for the apoptosis of retinal neuronal cells through the miR-345-5p/Atf1 axis. Therefore, the targeting of Mbd2 might represent a novel therapeutic strategy for the treatment of neurodegeneration in the early diabetic retina.